The downward continuation of the tilt angle. Issue 5 (1st June 2016) - Cooper, Gordon
ABSTRACT: The tilt angle filter T can be used both to enhance images of aeromagnetic data and as the basis of semi‐automatic interpretation methods. For vertically magnetised and vertically dipping contacts, rescaling T by factor α is equivalent to computing T from sources with all depths decreased by a factor α . This downward continuation is much less sensitive to noise than Fourier transform‐based downward continuation techniques, and because it reduces interference, it allows more accurate source depth determination from methods such as the tilt‐depth method. The method can be applied irrespective of the source and magnetisation type if the tilt angle of the analytic signal amplitude is used.